Effect of deltamethrin on reproductive performance in male zebrafish - S. T. Bhalerao; V.V. Karande; M.M. Gatne (Indian Journal of Veterinary and Animal Sciences Research, 2023)
The study was carried out on male zebrafish containing technical grade deltamethrin (98.5%). A total of 20 males were randomly divided into two groups (Group I) and Group II (Group II) and their pre-exposure spawn count, fecundity, and embryo mortality were calculated at weekly intervals within each group. Results show significant (p0.05 and 0.01) reduction in total count of embryos over 21 days in Group I. Similarly, in Group II it was 36.49 0.54, 72.740.09 and 86.370.06 at 7, 14 and 21 days respectively postexposure of males to deltamethionine.